Germplasm Seed Movement and Global Plant Health - Kumar, Lava; Kumari, Safaa (The International Society for Plant Pathology, 2023)
Global seed transfers through trade, and collection and distribution of genetic resources by genebanks are important pathways for the transboundary spread of seed-borne pests, especially viruses that the insect vectors can further transmit upon introduction. Various phytosanitary procedures, including the IPPC International Standard Phytosanitary Measures, have been established to minimize the risk of seed transmission and provide access to quality seeds crucial for food production and biodiversity conservation. This session will summarize the current state of efforts in minimizing the seed-transmission risk and measures to overcome bottlenecks to comply with phytosanitary standards. Presentations will cover pest risk to seed pathways and implications to global plant health, strategies for minimizing seed-transmission risk, advances in diagnostic techniques for characterization and sensitive detection of seed-borne pests, and efforts to enhance phytosanitary capacity, especially in low- and middle-income countries to enable safe seed exchanges. The session will also highlight policy and regulatory limitations/bottlenecks necessary to improve safe exchange of germplasm and boost seed trade.